Influence of soil solarization on the multiplication of aeroponic seed potato under net house (Gen-0) and open field conditions (Gen-1) of north central India - SADAWARTI, MURLIDHAR J; SAMADHIYA, R K; SINGH, R K; SHARMA, ASHWANI K; SINGH, S P; SHARMA, S K; BUCKSETH, TANUJA; KATARE, SUBHASH; SINGH, Y P; RAWAL, SANJAY; SINGH, VINAY; ROY, SATYAJIT; et al. (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was conducted at ICAR- CPRI, Regional Station, Gwalior, Madhya Pradesh to study the effect of soil solarization on weed population and multiplication of seed potatoes under aphid proof net house (Gen-0) and subsequently under field conditions (Gen-1) of 3 potato cultivars, viz. Kufri Mohan, Kufri Chipsona-1 and Kufri Lauvkar during 2017-18 and 2018-19. Treatments were replicated thrice in split plot design. The experimental area was solarized with black polythene and paddy straw mulch, whereas, unsolarized plots served as control. Mean monthly maximum temperature at all the soil depths was higher in polythene solarized plots followed by unsolarized and paddy straw mulch solarized plots under both net house and open field conditions. Soil nutrient properties, viz. pH, OC, available N, P and K were influenced by soil solarization both at planting and harvesting. Solarization with polythene and paddy straw mulch resulted in 88.23% and 41.05% reduction in weed population under net house and 74.80 and 37.79% reduction under open field conditions. Under net house conditions, total tuber yield was significantly higher with polythene solarization (29.33 t/ha), whereas, under open field conditions yield was maximum with paddy straw mulch (37.45 t/ha) over other two treatments respectively.